PERAN MOTIVASI KERJA, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI; Studi Pada Dinas Sosial Kota Tarakan - Muhammad Akbar (ECO-BUILD, 2026)
This study aims to examine the effects of work motivation, work environment, and job satisfaction on employee performance at the Tarakan City Social Service Office. The research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees and analyzed using multiple linear regression analysis. Prior to hypothesis testing, the data were subjected to validity and reliability tests, as well as classical assumption tests, including tests of normality, multicollinearity, and heteroscedasticity. The results show that, individually, work motivation, work environment, and job satisfaction have a positive and significant effect on employee performance. Furthermore, the simultaneous test results indicate that work motivation, work environment, and job satisfaction collectively have a positive and significant influence on employee performance at the Tarakan City Social Service Office. These findings suggest that enhancing work motivation, fostering a supportive work environment, and improving job satisfaction play an important role in improving employee performance. This study is expected to provide valuable insights for public sector organizations in their efforts to enhance employee performance.